Genetic diversity of Kappaphycus species (Gigartinales, Rhodophyta) in the Philippines. Issue 5 (2nd September 2016) - Dumilag, Richard V.; Orosco, Fredmoore L.; Lluisma, Arturo O.
Abstract : The mariculture of eucheumatoids (species of Kappaphycus and Eucheuma ) in the Philippines has had a long history, dating back to the 1970s. Over this period, a number of varieties have been brought into domestication; some are now widely distributed and farmed in various regions of the country, but a significant number appear to have a more restricted distribution and are farmed only in certain areas. The taxonomy of many of these seaweed cultivars and their phylogenetic relationships still remain to be resolved at the specific and subspecific levels. In this study, two mitochondrial DNA markers, COI-5P region and cox 2-3 intergenic spacer, were used to assess the genetic diversity of the farmed varieties and a few specimens collected from the wild. Analysis using haplotype networks revealed several new haplotypes for K. alvarezii, K. malesianus and K. striatus, mainly from specimens collected from eastern and southwestern regions of the Philippines. The inferred phylogenetic relationships based on both mtDNA markers resolved the identity of all the materials used in the study at the species level. We present molecular evidence that K. malesianus, in addition to K. alvarezii, K. cottonii, K. inermis, K. procrusteanus and K. striatus (and, hence, all currently recognized species of Kappaphycus ) occurs in the Philippines. Collectively, these observations suggest that the Philippine archipelago has richer genetic diversity of farmed and wild Kappaphycus than do the other geographic regions, consistent with the hypothesis that the Philippines is, or is part of, the centre of Kappaphycus biodiversity in the world. These findings also reveal an untapped diversity that can potentially be exploited for improving the commercial production of these carrageenophytes.